FIQH KEINDONESIAAN: Transformasi Hukum Islam Dalam Sistem Tata Hukum Di Indonesia - Tohari, Chamim (Analisis: Jurnal Studi Keislaman, 2015)
INDONESIAN JURISPRUDENCE: ISLAMIC LAW TRANSFORMATION   IN  LAW  SYSTEM  OF  INDONESIA.: This  study  discusses  about  the  idea  of  Islamic  law renewal in Indonesia,  as well as the  figures,  and it  makes  the  term  of Indonesian Jurisprudence   and  its  formalization   into  the  law system  of Indonesia.  The  purpose of this  study  is to  find  the answer  of these  following  points:  Firstly,  the interpretation or definition of Indonesian Jurisprudence concept; secondly, the figures who proposed Indonesian Jurisprudence and the result of their thoughts;  and the third, the formalization  of Jurisprudence concept  with  Indonesian  nuance  in the  law  system Indonesia. This study was a library research with a content analysis method. The results of this study are: (1) Indonesian Jurisprudence could be interpreted  as a Jurisprudence concept that is more Indonesian local-based; (2) Hasbi As-Shiddiqi  and Hazairin are two figures who proposed Indonesian Jurisprudence model, apart from other intellectuals. Hasbi is one of modernists  who offered his ideas comprehensively, started from his “Indonesian Jurisprudence” concept until the law renewal including its principle and method. Meanwhile Hazairin offered the development  of a new heritage system  which  interpreted   and  elaborated  based  on Al-Qur’an scriptural perception and Sunnah which is not a patrilineal system but bilateral family model); and (3) formalization  of Indonesian Jurisprudence   concept   produces   some   ordinance   regulation products  which are important  formally  and materially,  such as Ordinance  of Islamic Marriage Law, and also other  rules under the Ordinance, such as Government  Law, President  Instruction, and Supreme Court Law, as well as Islamic Law Compilation and Sharia Economic Law Compilation